aHIF but not HIF-1α transcript is a poor prognostic marker in human breast cancer - Cayre, Anne (BioMed Central, 2003)
BACKGROUND: Hypoxia-inducible factor-1α (HIF-1α) is part of a transcriptional factor that regulates genes involved in metabolic and vascular adaptation of tumours to oxygen restriction. A splicing variant lacking exon 14 (sHIF-1α) encodes a truncated protein that competes with the normal HIF-1α protein, decreasing its activity. A natural antisense transcript (aHIF) complementary to the 3'-untranslated region of HIF-1α mRNA was described recently. METHODS: With a semiquantitative multiplex reverse transcriptase–PCR (RT–PCR) assay, we assessed transcript concentrations of HIF-1α, sHIF-1α and aHIF in 110 patients with invasive breast carcinoma. RESULTS: We found a strong positive association between HIF-1α and sHIF-1α, sHIF-1α and aHIF, and an inverse correlation between HIF-1α /sHIF-1α and aHIF. aHIF transcript expression was associated with poor disease-free survival in univariate (P = 0.0038) and multivariate (P = 0.0016) analyses in this series of high-risk primary breast carcinomas. CONCLUSION: In our series of breast cancer patients, aHIF, and not HIF-1α transcript, is a marker of poor prognosis.